The Effect Of Original Local Government Revenue, General Allocation Funds, Specific Allocation Funds And Profit Sharing Funds On Economic Growth Mediated By Capital Expenditure In Districts/Cities In Central Java - Noor Rosyadi; Sunardi Sunardi; Edi Subiyantoro (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to examine the effect of original local government revenue, general allocation funds, specific allocation funds, and profit sharing funds on economic growth, both directly and through capital expenditure. The quantitative approach was carried out by census of 35 regencies/cities in Central Java, with a research period of 2018-2022, thus as many as 175 data. Direct influence testing uses multiple linear regression, while indirect influence is carried out with a sobel test that has first gone through various classical assumption tests. The results revealed that original local government revenue, and specific allocation funds have a positive and significant effect on capital expenditure, and only have a direct effect on economic growth. General allocation funds have no effect on capital expenditure, but have a direct impact on positive and significant direction on economic growth. Profit sharing funds actually have a negative and significant influence on capital expenditure, but do not affect economic growth. Similarly, capital expenditure also does not have an effect on regional economic growth, thus it is not able to become an intervening variable.